Percutaneous Nephrolithotomy versus Open surgery for Renal Calculi - Sawangsupakul, Wutta (Journal of Health Science of Thailand, 2018)
Percutaneous nephrolithotomy (PCNL) now is an acceptable form of surgical treatment for renal calculi and is associated with less morbidity and rapid convalescence comparing to the openstone surgery. To compare results and complications of PCNL and open surgery, a case-control study was performed by reviewing medical records of patients who underwent stone removal surgery between October 2005 and September 2008. There were a total of 79 patients, of which 41 had undergone PCNL and 38 open surgery. Statistical analysis was performed by descriptive statistics, chi-square test, and t-test. It was found that preoperative status of the two groups were similar. Only 7.32 percent of the PCNL group needed blood transfusion compared with 50 percent of the open surgery group which was statistically different (p < 0.01). Postoperative fever of the PCNL group and open surgery group were 22 percent and 50 percent respectively (p < 0.05). The number of doses of postoperative narcotic injection was lower in the PCNL group when compared with those of the open surgery group (mean 0.78 doses versus 2.39 doses, p < 0.01). Length of hospital stay was comparable between the two groups. The stone free rate of the PCNL group and the open surgery group were 68.29 percent and 78.95 percent respectively. The operative time of the PCNL group was longer when compared with the open surgery group (152 min vs 103 min, p < 0.01). Failure to access tract were reported in five patients in the PCNL group (12.2%) and underwent other procedure while no such case was reported in the open surgery group. Severe bleeding due to arteriovenous fistula occurred in one patient of the PCNL group and nephrectomy was done. PCNL is an effective method to treat renal calculi compared to open surgery but learning experience are critical to good outcomes.